Changes in sexual performance and biochemical characterisation of functional neural regions: A study in serotonin transporter knockout male rats. (30th April 2019) - Geng, Hao; Peng, Dangwei; Huang, Yuanyuan; Tang, Dongdong; Gao, Jingjing; Zhang, Yao; Zhang, Xiansheng
Abstract: To explore the correlation between SERT expression and sexual activities and seek the possible mechanism of SERT in regulating ejaculations, we analysed the sexual activities and biochemical characteristics of five measured neural regions in three rat genotypes ( SERT −/−, SERT +/− and SERT +/+ ). The results showed the SERT −/− group showed fewer ejaculations and a longer ejaculation latency than the SERT +/+ group, while the SERT +/− group did not differ significantly from the SERT +/+ group in sexual performance. In addition, the SERT −/− group showed an almost complete absence of SERT mRNA and protein expression in all measured regions. In the SERT +/− group, the SERT mRNA and SERT protein expressions were downregulated by approximately 50% and 35%, respectively, compared to the SERT +/+ group. The SERT −/− group had the highest 5‐HT levels, and the 5‐HT level in the SERT +/− group was between the other two groups. Besides, the 5‐HT levels differed in almost all measured regions of the three groups. Therefore, our study confirmed that SERT played a key role in sexual performance. A certain amount of SERT protein may be critical to normal sexual performance. Hence, Polymorphisms of the SERT gene should still be highlighted for ejaculation regulation research.